Una indústria na "aldeia": a génesis da ourivesaria no concello de Gondomar, Portugal - Sousa, Ana Cristina (2021)
Extending to the east of the city of Porto and following the Douro river to the south, the Gondomar's council is currently the largest center of gold production, a reality that earned it the epithet of the "goldsmith's capital". Predominantly rural until the end of the twentieth century, it has been differentiated at the industrial level, and since the eighteenth century, by the crafts of carpentry and goldsmithing, sectors that absorbed part of the workforce of a continuously growing active population. Based on the research carried out in the parish registers of the parishes of the council, in the commercial almanacs, in the registrations of goldsmiths' in the Porto Assay Office, in the military censuses, passport applications, other periodic publications and several interviews with artisans, with this article, we intend to explain some of the reasons that made possible the birth of an "Eldorado" in a predominantly agricultural scenario, marked by scarcity and poverty. The affirmation of family dynasties since the eighteenth century, the involvement of all in the production process and the practice of low-cost manufacturing, made possible by a clear and continuous exploitation of the manual labor, are among the justifications of this phenomenon.